Concept of Multi-Orientation Shipyard Industry Development Environmentally Friendly and Sustainable - Azhar, Ali; Harahab, Nuddin; Putra, Fadillah; Kurniawan, Andi; Poundra, Gde A Prabhawatya (International Journal of Marine Engineering Innovation and Research, 2024)
Indonesia's geographical conditions and position are very favorable and various policies from the government from 2005 until now are expected to become the shipyard industry to become a tough industry, but in reality it is still not as expected. The condition of the domestic shipyard industry in 2017 until now there is only ship repair and maintenance work, while orders for new ships or buildings are very few and even zero demand ship orders, causing business continuity in the shipyard industry to be disrupted and even out of business. This paper aims to develop a concept for the development of a multi-oriented shipyard industry that is environmentally friendly and sustainable. The preparation of this concept begins with identifying problems, collecting secondary data, reviewing related articles (shipyard industry, ship recycling yard industry, environment, sustainability, and supporting methods), analyzing and developing a development concept. The results obtained from drafting the concept are in the form of a diagrammatic model for the development of a multi-oriented shipyard industry that is environmentally friendly and sustainable. The development concept consists of (1) research background in the form of the existing conditions of the shipyard industry, ship recycling industry, geography, infrastructure, superstructure; (2) research that has been conducted in the form of relevant journal articles and proceedings; (3) research to be conducted in the form of sustainability criteria, orientation diversification and strategy selection; (4) implementation.